2020
DOI: 10.3390/jcm9020552
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Treatment Modulates Autophagy in Multiple Myeloma

Abstract: Although the introduction of bortezomib as a therapeutic strategy has improved the overall survival of multiple myeloma (MM) patients, 15–20% of high-risk patients do not respond to bortezomib over time or become resistant to treatment. Therefore, the development of new therapeutic strategies, such as combination therapies, is urgently needed. Methods: Given that bortezomib resistance may be mediated by activation of the autophagy pathway as an alternative mechanism of protein degradation, and that an enormous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 56 publications
2
58
0
Order By: Relevance
“…Here, KMS-20 cells presented a lower sensitivity to bortezomib and ixazomib than KMS-26 and KMS-28BM cells. Although proteasome β5 subunit overexpression and the induction of autophagy by a proteasome inhibitor have been associated with resistance in multiple myeloma (MM) cells [ 45 , 46 , 47 ], our results showed that there was no change in the expression level of the proteasome β5 subunit, inhibition level of proteasome β5 subunit activity, or degree of autophagy induction by bortezomib and ixazomib. These results suggest that a low sensitivity to bortezomib and ixazomib relies on other factors.…”
Section: Discussionmentioning
confidence: 61%
“…Here, KMS-20 cells presented a lower sensitivity to bortezomib and ixazomib than KMS-26 and KMS-28BM cells. Although proteasome β5 subunit overexpression and the induction of autophagy by a proteasome inhibitor have been associated with resistance in multiple myeloma (MM) cells [ 45 , 46 , 47 ], our results showed that there was no change in the expression level of the proteasome β5 subunit, inhibition level of proteasome β5 subunit activity, or degree of autophagy induction by bortezomib and ixazomib. These results suggest that a low sensitivity to bortezomib and ixazomib relies on other factors.…”
Section: Discussionmentioning
confidence: 61%
“…CQ and HCQ can enhance carfilzomib induced cell apoptosis by inhibition of autophagy toward MM (Jarauta et al, 2016;Baranowska et al, 2016). The cytotoxicity of bortezomib on MM also can be augmented by Baf1, HCQ, or macrolide antibiotics via inhibiting prosurvival autophagy in cotreatment manner (Di Lernia et al, 2020;Miyazawa, 2011;Moriya et al, 2013). Moreover, 3-MA promoted sensitivity of glioblastoma cells to bortezomib by inhibition of bortezomib induced cytoprotective autophagy .…”
Section: Proteasome Inhibitorsmentioning
confidence: 98%
“…Assessing oxygenation in the different layers of tumour pinpoint that there is a progressive increase of nutrient and oxygen levels across the inner depth [ 162 ], thus fueling genomic instability [ 163 ], the cancer progression (PD) [ 16 ], the switch to anaerobic metabolism [ 164 ], as well as the epithelial–mesenchymal transition, metastases [ 165 ], and the induction of cancer “stem cell” phenotype [ 166 ]. Hypoxia is a hallmark of cancer, inducing many abnormalities with prognostic consequences linked to defects in apoptosis and autophagy [ 167 , 168 ] and the resistance to radio-chemotherapy [ 169 , 170 , 171 ] and immunotherapy [ 13 , 172 , 173 ] likewise hamper the cancer aggressive phenotype acquisition, while shaping a pro-angiogenic, inflamed, and immunosuppressive neoplastic ecosystem [ 154 , 174 , 175 ]. Consequently, it is necessary either to target many different actors on the scene within the neoplastic niche or attempt to homogenize the cancer heterogeneity [ 161 ].…”
Section: Boosting Cancer Immunotherapy Using Anti-angiogenics: Thementioning
confidence: 99%